Quantifying the burden of rhodesiense sleeping sickness in Urambo District, Tanzania - Matemba, L.E.; Fèvre, Eric M.; Kibona, S.N.; Picozzi, K.; Cleaveland, S.; Shaw, A.P.M. (Public Library of Science, 2010)
Human African trypanosomiasis is a severely neglected vector-borne disease that is always fatal if untreated. In Tanzania it is highly focalised and of major socio-economic and public health importance in affected communities.